Pedagogical Insights from Al-Mawahib Al-Rabbaniyah: Enhancing Arabic Grammar Learning through the Nazm of Al-Ajrumiyyah - Solehudin, Muhamad; hanifansyah, Nur (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
This study explores the pedagogical effectiveness of Nazm Al-Ajrumiyyah and its commentary Al-Mawahib Al-Rabbaniyah in enhancing the learning of Arabic grammar, particularly in the areas of nahwu (syntax) and sharaf (morphology). Utilizing a mixed-method approach, the research involves 200 students from Pon Pes Darullughah Wadda'wah and 100 students from the Arabic Language Education (PBA) department. Quantitative results indicate significant improvement in students' memorization and understanding of grammatical rules after incorporating nazm into their curriculum, with 75% of learners showing enhanced long-term retention. Qualitative findings, based on classroom observations and interviews, reveal that students found the poetic method engaging and effective in simplifying complex grammar concepts. The rhythmic structure of nazm facilitated a more interactive and enjoyable learning experience, while Al-Mawahib Al-Rabbaniyah provided valuable explanations that bridged traditional grammatical rules with contemporary learning needs. The study concludes with recommendations for curriculum development, advocating for the formal integration of nazm in Arabic grammar instruction to improve comprehension and retention.